Dampak Praktik Poligami terhadap Interaksi Muamalah dalam Keluarga - Erna Sri Mardani; Riski Ferdiansyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Polygamy is a topic in the study of Islamic Family Law that continues to attract attention for discussion. This is due to the polemics related to polygamy, both from a theological and anthropological perspective. Starting from such problems, this then led the researchers to analyze the impacts arising from social and economic aspects, how to review Islamic law regarding the practice of polygamy and its implementation in society. The researcher used the library research method, where the researcher collected information by studying theories from various references related to research (qualitative). The type of data that researchers use is secondary data, which is data that comes from document data. Document data defined here is data originating from books, research reports, journals, etc. (qualitative). The research results show that the practice of polygamy according to state law and Islamic law is permitted, provided that they are able to fulfill their rights and obligations, are able to act fairly, and are mentally and financially mature. The practice of polygamy has positive and negative impacts, the negative impact of the practice of polygamy if you are unable to carry it out, which has an impact on the wife, children and husband who carry it out. So researchers hope that practitioners of polygamy will consider various aspects before deciding to practice polygamy in order to maintain harmony in the household.